PRONAF: sua operação e indicação de distorções - Cabral, Mayra dos Santos (2001)
We analvzed the agriculture modernization matter and the reform of Rural Credit National System - SNCR, and the conservative logic of both process. The target of this ransom was to show the integration or the farmer matter to the agroindustries and to the technology was, since that time, a very important point to the agriculture credit acess. We showed the slowly Goverment leaving of the Rural Credit, verifying the resources fali from the Tfaditionals Sources and the partial substitution of these resources to fmance New Sources In this context, we analyzed, the family farmer like a public without approach to the Rural Credt and the Monetary Authorities indication about introducing specifíc politics for this public. For this purpose, we used the results we got through the studies that INCRA joined FAO did from 1994 to 1996. So, we analyzed the PRONAF - National Program for Family Agriculture Strengthening, even so its performance between 1995 and 1999 years. In th is anãlysis, we made clear that the logic remainded the same logic of SNCR reform: the family farmers who were joined to the agroindustries and have technology, get acess to the Rural Credit and, those who are out of the agriculture modernization weep out of this approach We detached the concentration of discharging resources in some regions in the countrv and in products which are joined to the agroindustries . Finally. the difficulties the family'farmers got about finance costs and guarantee that are required for fmancing; the family farmer new situation about disconnect rural activities; and the Agriculture Reform placed which, since 1999, had being considered a PRONAF beneficiary.